Early myeloid lineage choice is not initiated by random PU.1 to GATA1 protein ratios - Hoppe, P; Schwarzfischer, M; Loeffler, D; Kokkaliaris, K; Hilsenbeck, O; Moritz, N; Endele, M; Filipczyk, A; Gambardella, A; Ahmed, N; Etzrodt, M; Coutu, D; et al. (Nature Publishing Group, 2016)
The mechanisms underlying hematopoietic lineage decisions remain disputed. Lineage affiliated transcription factors (TFs) with the capacity for lineage reprogramming, positive auto-regulation and mutual inhibition have been described to be expressed in uncommitted cell populations. This has led to the assumption that lineage choice is cell-intrinsically initiated and made by stochastic switches of randomly fluctuating cross-antagonistic TFs. However, this hypothesis was developed based on RNA expression data from snapshot and/or population average analyses. Alternative models of lineage choice can therefore not be excluded. Here, we use novel reporter mouse lines and live imaging for continuous single cell long-term quantification of PU.1 and GATA1 TF protein levels. We analyse individual hematopoietic stem cells (HSCs) throughout their differentiation into megakaryocytic/erythroid (MegE) and granulocytic/monocytic (GM) lineages. The observed expression dynamics are incompatible with the assumption that stochastic switching between PU.1 and GATA1 precedes and initiates GM versus MegE lineage decision making. Rather, they suggest their involvement only in executing and locking down lineage choice once made. The current prevailing model on early myeloid lineage choice will thus have to be revised.